13 Things mentally strong people don't do - Morin, Amy (Harper, 2015)
Expanding on her viral post that has become an international phenomenon, a psychotherapist offers simple yet effective solutions for increasing mental strength and finding happiness and success in life.As a licensed clinical social worker, college psychology instructor, and psychotherapist, Amy Morin has seen countless people choose to succeed despite facing enormous challenges. That resilience inspired her to write 13 Things Mentally Strong People Don't Do, a web post that instantly went viral, and was picked up by the Forbes website.Morin's post focused on the concept of mental strength, how mentally strong people avoid negative behaviors--feeling sorry for themselves, resenting other people's success, and dwelling on the past. Instead, they focus on the positive to help them overcome challenges and become their best.In this inspirational, affirmative book, Morin expands upon her original message, providing practical strategies to help readers avoid the thirteen common habits that can hold them back from success. Combining compelling anecdotal stories with the latest psychological research, she offers strategies for avoiding destructive thoughts, emotions, and behaviors common to everyone.Like physical strength, mental strength requires healthy habits, exercise, and hard work. Morin teaches you how to embrace a happier outlook and arms you to emotionally deal with life's inevitable hardships, setbacks, and heartbreaks--sharing for the first time her own poignant story of tragedy, and how she summoned the mental strength to move on. As she makes clear, mental strength isn't about acting tough; it's about feeling empowered to overcome life's challenges.